1999
DOI: 10.1116/1.581582
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous recombination of atomic bromine and fluorine

Abstract: Recombination coefficients (γ) of Br and F atoms have been measured for crystalline Si, quartz, photoresist, anodized aluminum, poly-Si, WSix, tungsten and stainless steel surfaces for a range of temperatures. The γBr and γF values are compared to our previously reported measurements of γCl [G. P. Kota, J. W. Coburn, and D. B. Graves, J. Vac. Sci. Technol. A 16, 270 (1998)]. In general, the Br-, Cl- and F-atom recombination coefficients decrease as the surface temperature increases. The γBr values are similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(14 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…where c F is the probability of heterogeneous recombination for fluorine atoms (c F % 0:05 from [22]), D F the effective diffusion coefficient and k is the effective diffusion length. Effective diffusion coefficients are represented by the combination of free diffusion coefficient and inter-diffusion coefficient, calculated using the Chapman-Enscog equation [10,21] while the effective diffusion length is determined by the given reactor axial and radial sizes [16].…”
Section: Gas Phase Compositionmentioning
confidence: 99%
“…where c F is the probability of heterogeneous recombination for fluorine atoms (c F % 0:05 from [22]), D F the effective diffusion coefficient and k is the effective diffusion length. Effective diffusion coefficients are represented by the combination of free diffusion coefficient and inter-diffusion coefficient, calculated using the Chapman-Enscog equation [10,21] while the effective diffusion length is determined by the given reactor axial and radial sizes [16].…”
Section: Gas Phase Compositionmentioning
confidence: 99%
“…The rate coefficients of heterogeneous recombination for H and Br atoms were obtained using k S ¼ ½ðà 2 =DÞ þ ð2r=v T Þ, 13) where D is the effective diffusion coefficient, 14,15) is the recombination probability, à À2 ¼ ð2:405=rÞ 2 þ ð=lÞ 2 is the effective diffusion length, 15) and v T ¼ ð8k B T=mÞ 1=2 . Since the recombination probabilities of both Br and H atoms in the HBr plasma are not known, we used the values recommended for pure Br 2 and H 2 gases ( Br % 0:2 16) and H % 0:05 17) ). When writing the kinetic equations for positive ions, we used k S ¼ v=d c , where d c ¼ 0:5rl=ðrh l þ lh r Þ.…”
Section: Zero-dimensional (Global) Plasma Modelmentioning
confidence: 99%
“…17,59) This suggests that the etching rates of Al 2 O 3 and SiO 2 are similar in HBr/Ar plasma and that the Br surface loss originating from the etching process is similar for these two materials. Kota et al have reported that the recombination coefficient of Br radicals on Al 2 O 3 is larger than that on SiO 2 , 60) and the difference in the Br radical density between Si and Al 2 O 3 wafers in the present study might be understood by the difference in the Br radical surface recombination probability. Figure 8 shows the dependence of the Br radical density on the bias voltage applied to the blanket Si wafer at O 2 flow rates of 0, 6, and 24 sccm.…”
Section: Resultsmentioning
confidence: 42%